Numerical simulation of cooling performance in microchannel heat sinks made of AlN ceramics - Vaferi, Kourosh; Vajdi, Mohammad; Nekahi, Sanam; Nekahi, Sahar; Moghanlou, Farhad Sadegh; Azizi, Shahla; Asl, Mehdi Shahedi (Springer Heidelberg, 2023)
The problem of generating a high amount of heat in microelectronic equipment should be minimized properly. Allowing systems to run for long periods of time in high temperatures can reduce the performance and reliability of equipment. The microchannel heat sink is an efficient cooling technology to prevent the generation of very high heat fluxes. In the present study, the effect of the applied heat fluxes and geometric parameters such as rib width on the entire thermal resistance and cooling capacity of the heat sink is examined numerically. Besides, the substrate's material changed from silicon to AlN ceramic. Because of the higher thermal conductivity of AlN, a more unfluctuating temperature distribution in the battom wall and a reduction of about 31% in the entire thermal resistance of the heat sink are reported. Additionally, the entire thermal resistance of heat sinks is greatly dependent on its geometric parameters such as rib width. Reducing the rib width results in a considerable diminish in total thermal resistance and betterment in the cooling capacity of the microchannel heat sink.
Keywords: Thermal Performance; Transfer Enhancement; Optimization; Design; Flow; Conductivity; Parameters